Cobalt chloride has beneficial effects across species through a hormetic mechanism - Schiavi, Alfonso; Runci, Alessandra; Maiorino, Teresa; Naso, Francesco Davide; Barenys, Marta; Fritsche, Ellen; Strappazzon, Flavie; Ventura, Natascia (Frontiers in Cell and Developmental Biology, 2022)
Severe oxygen and iron deficiency have evolutionarily conserved detrimental effects, leading to pathologies in mammals and developmental arrest as well as neuromuscular degeneration in the nematode Caenorhabditis elegans. Yet, similar to the beneficial effects of mild hypoxia, non-toxic levels of iron depletion, achieved with the iron chelator bipyridine or through frataxin silencing, extend C. elegans lifespan through hypoxia like-induction of mitophagy. While the positive health outcomes of hypoxia preconditioning are obvious, its practical application is rather challenging. Here, we thus test the potential beneficial effects of non-toxic, preconditioning interventions acting on iron instead of oxygen availability. We find that limiting iron availability through the iron competing agent cobalt chloride has evolutionarily-conserved dose-dependent beneficial effects: while high doses of cobalt chloride have toxic effects in mammalian cells, iPS-derived neurosphere and in C. elegans, sub-lethal doses protect against hypoxia- or cobalt chloride-induced death in mammalian cells and extend lifespan and delay age-associated neuromuscular alterations in C. elegans. The beneficial effects of cobalt chloride are accompanied by activation of protective mitochondrial stress response pathways.